Genetic signatures of a range expansion in natura: when clones play leapfrog. Issue 18 (26th August 2016) - Becheler, Ronan; Xhaard, Constance; Klein, Etienne K.; Hayden, Katherine J.; Frey, Pascal; De Mita, Stéphane; Halkett, Fabien
Abstract : The Durance River valley is annually invaded by a plant pathogen, the poplar rust fungus. We monitored both disease dynamics and genetic structure resulting from a colonization event. We found that genetic differentiation went hand in hand with a decrease in genotypic diversity. Moreover, we observed a patchy distribution of clonal lineages which pointed to leapfrog dispersal. Abstract: The genetic consequences of range expansions have generally been investigated at wide geographical and temporal scales, long after the colonization event. A unique ecological system enabled us to both monitor the colonization dynamics and decipher the genetic footprints of expansion over a very short time period. Each year an epidemic of the poplar rust ( Melampsora larici‐populina ) expands clonally and linearly along the Durance River, in the Alps. The colonization dynamics observed in 2004 showed two phases with different genetic outcomes. Upstream, fast colonization maintained high genetic diversity. Downstream, the colonization wave progressively faltered, diversity eroded, and differentiation increased, as expected under recurrent founder events. In line with the high dispersal abilities of rust pathogens, we provide evidence for leapfrog dispersal of clones. Our results thus emphasize the importance of colonization dynamics in shaping spatial genetic structure in the face of high gene flow.